2018
DOI: 10.7494/jcme.2018.2.2.38
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Molding Sand Elasticity

Abstract: The progressive mechanization and automation of industrial equipment is the driving force of progress, not only in the field of production but also in the measuring and control equipment. In mold production, the automation of processes such as forming molds and cores along with their assembly has led to increases in serial production, reductions in defects, and the shortening of molding times, among others. Thanks to automation in mold and core departments and the use of all sorts of manipulators, mold product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…450°C. This means that the loss of PCL specimen weight begins much later than in commonly used moulding sand foundry resins and is more violent [9]. The thermal destruction of two-component adhesives process is similar to the TG curve of pure furfuryl resin (Fig.…”
Section: Measurements and Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…450°C. This means that the loss of PCL specimen weight begins much later than in commonly used moulding sand foundry resins and is more violent [9]. The thermal destruction of two-component adhesives process is similar to the TG curve of pure furfuryl resin (Fig.…”
Section: Measurements and Discussionmentioning
confidence: 52%
“…2. DTA curves of applied resins [9] The study showed that the phenol-furfuryl resin has a lower temperature of the beginning of thermal destruction (temperature approx. 120°C).…”
Section: Measurements and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An optimisation of the production process of cores by blowing methods contains the selection of work parameters of the core box filling and moulding sand compaction processes as well as methods of moulding sand hardening by gaseous or thermal agents. Out of the parameters deciding on the processes of the mould cavity filling and moulding sand compaction the influence of such factors as: kind of the core sand and its reclaim [1][2][3][4][5][6][7][8][9], complication of the core shape, shooting pressure value, recommended surfaces and dimensions of shooting and venting holes, should be taken into account. The mentioned subjects, concerning traditional core binders (oil or linseed varnish, water glass, some resins for the hot-box process), were previously investigated [10][11][12][13][14][15][16][17][18], while analogous investigations for core sands with the inorganic Cordis binder -introduction of which into the foundry practice holds promise of decreasing pollution of the natural environment -were not performed.…”
Section: Introductionmentioning
confidence: 99%